2014
DOI: 10.1063/1.4883259
|View full text |Cite
|
Sign up to set email alerts
|

Electric field-induced magnetic switching in Mn:ZnO film

Abstract: A large magnetic modulation, accompanied by stable bipolar resistive switching (RS) behavior, was observed in a Mn:ZnO film by applying a reversible electric field. A significant enhancement of the ferromagnetism of the film, to about five times larger than that in the initial (as-grown) state (IS), was obtained by switching the film into the low resistance state. X-ray photoelectron spectroscopy demonstrated the existence of abundant oxygen vacancies in the IS of the film. We suggest that this electric field-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
26
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(30 citation statements)
references
References 21 publications
2
26
0
2
Order By: Relevance
“…No forming process is required for the devices, which may indicate the pre‐existence of V O in the as‐deposited films . The pure ZnO‐based device exhibits bipolar RS behavior, which is in agreement with previous reports from our research group . The SET voltage ( V SET ) and the RESET voltage ( V RESET ) of the ZnO‐based memory device are 0.88 and –0.82 V, respectively, which are similar to or even lower than those of previously reported memory devices based on the ZnO film .…”
supporting
confidence: 91%
“…No forming process is required for the devices, which may indicate the pre‐existence of V O in the as‐deposited films . The pure ZnO‐based device exhibits bipolar RS behavior, which is in agreement with previous reports from our research group . The SET voltage ( V SET ) and the RESET voltage ( V RESET ) of the ZnO‐based memory device are 0.88 and –0.82 V, respectively, which are similar to or even lower than those of previously reported memory devices based on the ZnO film .…”
supporting
confidence: 91%
“…The Zn 2 p 3/2 and Zn 2 p 1/2 states have been found at 1021.3 and 1044.2 eV, respectively, which indicates that zinc ion was bound to oxygen in the form of ZnO. These two values were smaller than those obtained for ZnO bulk values (1022.2 and 1045 eV, respectively), which indicates that the ZnO films was oxygen deficiency . This was corroborated by the binding energy (BE) values of the Zn 2 p 3/2 state of the ZMO thin film, which were smaller than those of the ZnO thin films; this is clear evidence for the existence of a significant oxygen deficiency in the ZMO thin film.…”
mentioning
confidence: 98%
“…[21][22][23][24][25][26][27][28] The electric manipulation of ferromagnetic properties (such as magnetization, magnetic anisotropy, and Curie temperature) has been found in dilute magnetic semiconductors (DMS) doped with magnetic element. [26][27][28][29][30][31][32][33] It was showed that electric field could induce room temperature ferromagnetism in low carrier paramagnetic Ti 0.9 Co 0.1 O 2 film with an electric EDLT using liquid electrolyte. 28 The reversible magnetization modulation accompanied with stable bipolar RS has also been observed in some DMS oxide films such as Co:ZnO, 29 Mn:ZnO, 30,31 and Mn:TiO 2 , 32 in the framework of RRAM device.…”
mentioning
confidence: 99%
“…[26][27][28][29][30][31][32][33] It was showed that electric field could induce room temperature ferromagnetism in low carrier paramagnetic Ti 0.9 Co 0.1 O 2 film with an electric EDLT using liquid electrolyte. 28 The reversible magnetization modulation accompanied with stable bipolar RS has also been observed in some DMS oxide films such as Co:ZnO, 29 Mn:ZnO, 30,31 and Mn:TiO 2 , 32 in the framework of RRAM device. The bound magnetic polarons (BMPs) on the basis of the coupling between the electrons trapped by oxygen vacancies and magnetic ions is commonly used to explain ferromagnetic ordering in oxide DMSs.…”
mentioning
confidence: 99%
See 1 more Smart Citation